2009
DOI: 10.1007/s10705-009-9277-4
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and nitrogen cycles in the vegetation of differently managed buffer zones

Abstract: Vegetated buffer zones (BZs) between a cultivated field and a watercourse reduce erosion and load of particle-bound phosphorus (P), but decay of abundant vegetation increases the potential of BZs to act as a source of readily algal-available P. To quantify temporal variations in P and nitrogen (N)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
1
28
0
2
Order By: Relevance
“…Harvest of plants is recommended in buffer zones to reduce the risk of P leaching after frost (UusiKämpä 2005; Räty et al 2010). However, harvesting alone may not solve all the problems with the risk of P leaching, since plant roots remain after harvest.…”
Section: Phosphorus Release In Relation To Different Combinations Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Harvest of plants is recommended in buffer zones to reduce the risk of P leaching after frost (UusiKämpä 2005; Räty et al 2010). However, harvesting alone may not solve all the problems with the risk of P leaching, since plant roots remain after harvest.…”
Section: Phosphorus Release In Relation To Different Combinations Of mentioning
confidence: 99%
“…Phosphorus released from plant tissues is of especially high relevance in conditions with repeated freezing and thawing of plants and soil during winter. Losses of P from shoots after frost damage have been reported, for instance, for native prairie vegetation (White 1973), grassland (Uhlen 1989), alfalfa and grasses (Timmons et al 1970;Roberson et al 2007), vegetated buffer zones/strips consisting of grasses and other plant species (Räty et al 2010), and different species of catch/cover crops (Miller et al 1994;Bechmann et al 2005;Sturite et al 2007). However, most of these studies examined only aboveground parts of the plants and few studies have included plant roots damaged by frost (De Baets et al 2011;Kreyling et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have shown a greater proportion of biomass TP released as WEP (e.g. Räty et al, 2010), the results from this study correspond directly to the work of others (e.g. Øgaard, 2015;Roberson et al, 2007).…”
Section: Greenhouse Experimentssupporting
confidence: 88%
“…When plants begin to decompose, they return P to the soil, and if not incorporated into the deeper soils, this P now contained within the soil can move into adjacent water bodies during major hydrologic events through dissolution or erosion (Räty, Uusi-Kämppä, Yli-Halla, Rasa, & Pietola, 2010).…”
Section: Plant Uptake Of Phosphorusmentioning
confidence: 99%
“…Organic carbon content and soil moisture at the time of sampling were highest in the natural site due to permanent vegetation cover and abundant decaying plant material (Räty et al, 2010b). The total porosity and macro porosity were generally high in all studied sites.…”
Section: General Physical Propertiesmentioning
confidence: 86%